SYSTEMATIC LITERATURE REVIEW EFFECTIVENESS OF WHISTLEBLOWING SYSTEMS IN PREVENTING AND DETECTING WHITE-COLLAR CRIME AND FRAUD: INSIGHTS FROM GLOBAL AND REGIONAL PERSPECTIVES - Eni Nur Hayati; Abdul Rohman; Sari Lestari (Politeknik Negeri Semarang, 2026)
Abstract: Whistleblowing systems have emerged as pivotal mechanisms for mitigating white-collar crime and fraud, yet their effectiveness remains underexplored across diverse global and regional contexts. This systematic literature review (SLR) synthesizes 45 peer-reviewed studies published between 2015 and 2025, employing PRISMA guidelines to evaluate the design, implementation, and outcomes of these systems. Novelty lies in the integration of economic theory of crime with regional comparative analysis, revealing that while global frameworks like the OECD Anti-Bribery Recommendation enhance detection rates by up to 30% in high-income countries, regional disparities—such as weaker protections in emerging economies like the Adriatic region—result in 40-50% lower reporting efficacy. Findings underscore barriers like retaliation fears and cultural stigma, alongside enablers such as financial incentives under the U.S. Dodd-Frank Act. This review offers actionable insights for policymakers, proposing a hybrid model blending economic incentives with culturally adaptive protections to bridge global-regional gaps, potentially reducing undetected fraud by 25% worldwide. Keywords: fraud detection, whistleblowing systems, white-collar crime, global perspectives, regional disparities